Comparison of Vitamin D Level in Preterm and Term Infant-Mother Pairs: A Brief Study - Minoo Fallahi; Abolfazl Afjeh; Hedieh Saneifard; Navid Namazi; Mohammad Kazemian; Shahrzad Tabatabaee (Mashhad University of Medical Sciences, 2016)
Background: Recent studies have demonstrated the high prevalence of vitamin D deficiency in the general population. Pregnancy and preterm delivery are known as risk factors for vitamin D deficiency. Consequently, vitamin D level in women with preterm deliveries might vary from those with term pregnancies. In this study, we aimed to compare vitamin D level in term and preterm infant-mother pairs. Methods: This cross-sectional study was conducted in the neonatal intensive care unit of Mahdieh Hospital in Tehran, Iran in 2013. Serum level of 25-hydroxy vitamin D in preterm infant-mother pairs (≤ 32 weeks of gestation and birth weight ≤ 1500 g) was compared with term infant-mother pairs within the first 24 hours after delivery. Results: In total, 62 infant-mother pairs were recruited in this study, including 33 preterm (53.2%) and 29 term (46.8%) newborns; overall, 32 (51.6%) infants were male. the mean maternal age was 27.3 years in the preterm group and 26.4 years in the term group. The mean serum vitamin D level in preterm infants was 13.91 ng/ml. In the preterm group, vitamin D level was within the range of 4-59 ng/ml in newborns and 8-62 ng/ml in mothers. In the term group, the mean vitamin D level was 13.39 in infants and 13.7 ng/ml in mothers. In total, 48.5% and 65.5% of preterm and term groups had vitamin D deficiency, respectively. Among all newborns, 56% had vitamin D deficiency, although the difference between term and preterm neonates was not statistically significant. Also, there was no significant correlation between the infants' serum vitamin D level and birth weight. Based on the findings, serum vitamin D levels in mothers and newborns were significantly correlated (P